1994
DOI: 10.1111/j.1365-2109.1994.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating and spawning of freshwater crayfish, Austropotamobius pallipes Lereboullet, under laboratory conditions

Abstract: The study includes mating and spawning data of freshwater crayfish, Austropotamobius pallipes Lereboullet, obtained in four consecutive years (1987)(1988)(1989)(1990). A total number of 586 wild-caught female A. pallipes in the 21-65 mm to 45-60mm carapace length (CL) size were held under laboratory conditions at different dates in September-October. Initial densities at mating time were 21 and 24 erayfish/m' with a 1:2 malc:female ratio. High percentages of mating were obtained (97 4-100%) exeept in 1989 (57-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
2
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 8 publications
6
33
2
1
Order By: Relevance
“…Values of correlations between measured parameters are shown in Table III while the relations between females and their eggs are shown on Figures 1a, b, c, and d. The existence of positive correlation between female size and total number of eggs they produce is known from the literature (HUNER and LINDQVIST, 1991). Contrary to HARLIOĞLU (1996) andHARLIOĞLU andTÜRGÜLÜ, (2000), and similar to RHODES and HOLDICH (1982), BREWIS and BOWLER (1985), KÖKSAL (1988), TAUGBØL, SKURDAL and FJELD (1988), CARRAL et al (1994, 2004, STUCKI (1999), and EVERSOLE et al (2002, we found positive correlation between female size and number of eggs. Correlation coefficients reported by RHODES and HOLDICH (1982), BREWIS and BOWLER (1985) and CARRAL et al (1994) showed a great variability (0.39-0.93).…”
Section: Resultscontrasting
confidence: 52%
See 4 more Smart Citations
“…Values of correlations between measured parameters are shown in Table III while the relations between females and their eggs are shown on Figures 1a, b, c, and d. The existence of positive correlation between female size and total number of eggs they produce is known from the literature (HUNER and LINDQVIST, 1991). Contrary to HARLIOĞLU (1996) andHARLIOĞLU andTÜRGÜLÜ, (2000), and similar to RHODES and HOLDICH (1982), BREWIS and BOWLER (1985), KÖKSAL (1988), TAUGBØL, SKURDAL and FJELD (1988), CARRAL et al (1994, 2004, STUCKI (1999), and EVERSOLE et al (2002, we found positive correlation between female size and number of eggs. Correlation coefficients reported by RHODES and HOLDICH (1982), BREWIS and BOWLER (1985) and CARRAL et al (1994) showed a great variability (0.39-0.93).…”
Section: Resultscontrasting
confidence: 52%
“…Contrary to HARLIOĞLU (1996) andHARLIOĞLU andTÜRGÜLÜ, (2000), and similar to RHODES and HOLDICH (1982), BREWIS and BOWLER (1985), KÖKSAL (1988), TAUGBØL, SKURDAL and FJELD (1988), CARRAL et al (1994, 2004, STUCKI (1999), and EVERSOLE et al (2002, we found positive correlation between female size and number of eggs. Correlation coefficients reported by RHODES and HOLDICH (1982), BREWIS and BOWLER (1985) and CARRAL et al (1994) showed a great variability (0.39-0.93). CARRAL et al (2004) explains that probable cause of correlation coefficient variability is related to the different number of animals, the number of populations, number of reproductive season and the phase of embryonic development taken into consideration.…”
Section: Resultscontrasting
confidence: 52%
See 3 more Smart Citations